Prospective evaluation of extended reality for neonatal intubation education - Donnchadh O'Sullivan; Tomas Leng; Christopher Bosley; Amelia Barwise; Raymond Stetson; Yue Dong; Stephanie Mavis; Venkatesh Bellamkonda; Christopher Colby; Brian Pickering (Springer, 2024)
Abstract Purpose 360° immersive videos may be useful in procedure-based healthcare settings. We hypothesized that extended reality (XR) neonatal intubation education is a feasible alternative to live demonstration in skill and knowledge transfer. Methods This was a prospective single center evaluation of an educational XR intubation video using Premature Anne™ (Laerdal Medical, Stavanger, Norway) comparing to a live demonstration. Participants were randomly allocated to either live demonstration or XR group. Each group received 20 min of teaching from the pediatric respiratory care education specialist, either in person or in video format. Intubation success, knowledge and skill acquisition were measured using a questionnaire and checklist. Results We had a total of 23 participants, XR (n = 11) and live demonstration (n = 12). The groups were heterogeneous in experience level.The XR group was successful at intubating 73% of the time (n = 8), which was not significantly different to the live demonstration group 58% (n = 7) (p = 0.667). For patients who achieved intubation, there was no difference between groups in the mean time to successful intubation; 98 s (SD 73) for the XR group and 65 s (SD 22) for the live demonstration group (p = 0.685).When comparing scores between groups there were no statistically significant differences regarding knowledge scores (p = 0.514), skill scores (p = 0.826) and total scores (p = 0.926). Conclusion These preliminary findings indicated no significant differences between the XR and live demonstration groups in terms of intubation success, knowledge acquisition, skill performance, total scores or time to successful intubation.